Modern ideas about the role of the galaninergic system in the pathogenesis of heart failure and myocardial remodeling - A. A. Yafarova; A. R. Kiselev; A. F. Sheptulina; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Despite advances in diagnosis and treatment, heart failure (HF) still remains one of the unsolved problems of modern cardiology. The appearance and progression of HF is preceded by the development of maladaptive myocardial remodeling. In this regard, the search for new molecules for therapeutic action aimed at preventing myocardial remodeling is of undoubted interest. In this context, the galaninergic system seems to be a promising target. To date, evidence has been accumulated that activation of the galaninergic system leads to an increase in cardiomyocyte protection in the early stages after myocardial injury. It has been shown that galaninergic cascades can influence myocardial remodeling, including cell death, cardiomyocyte hypertrophy, and fibrosis. Various experimental models of heart damage showed that under stress conditions and the action of galanin and its derivatives, carbohydrate metabolism in cardiomyocytes improved, oxidative stress decreased due to antioxidant effect, and hyperproduction of reactive oxygen species by mitochondria decreased. Data were also obtained that galaninergic cascades prevent cardiomycyte hypertrophy by suppressing the expression of some fetal genes. This review article describes the currently studied cellular and molecular effects of galanin on the cardiovascular system, as well as data on the role of the galaninergic system in the pathogenesis of myocardial remodeling.